Faktor-Faktor yang Mempengaruhi Kinerja Sistem Informasi Akuntansi: Partisipasi Pemakai Sistem Informasi Akuntansi, Kemampuan Pemakai Sistem Informasi Akuntansi, Ukuran Organisasi, dan Program Pelatihan Pendidikan - Sela Dwi Putri; Cris Kuntadi; Rachmat Pramukty (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Â Accounting information systems are very important in institutions to support the smooth performance of institutions, assessing the performance of an institution requires good and complete financial reports, therefore an accounting information system is also needed which is supported by computerized information technology. Previous research or relevant research serves to strengthen the theory and phenomena of the relationship or influence between variables. This article reviews the factors that influence the performance of accounting information systems, namely the participation of users of accounting information systems, the ability of users of accounting information systems, organizational size, and educational training programs from a study of accounting information systems literature. The purpose of writing this article is to build a hypothesis on the influence between variables to be used in further research. The results of this literature review article are: 1) Participation of users of accounting information systems affects the performance of accounting information systems; 2) The ability of users of accounting information systems affects the performance of accounting information systems; 3) Organizational size affects the performance of accounting information systems and 4) Educational training programs affect the performance of accounting information systems